Mechanical And Acoustic Properties Of Nonwoven Needle Punched Flax Fibre Mat- Acrodur Resin Composite - Soo, Hui Fen (Universiti Sains Malaysia, 2017)
The effect of processing method on the mechanical and acoustic properties of nonwoven flax fibre mat/Acrodur resin was studied. The prepregs were produced using both impregnation line and hand lay-up methods, then compressed into composites with the same thickness of 1 mm. The mechanical properties of the composites were characterized by tensile, flexural and fracture toughness tests, while the morphological properties were characterized by scanning electron microscope (SEM). Also, acoustic properties were determined using impedance tube. The tensile and flexural properties, as well as fracture toughness were found to be better in composites manufactured from impregnation method. However, the composites prepared from hand lay-up method have higher void content, which results in better acoustic absorption. Besides that, the effect of anisotropy on mechanical properties were studies, but there was no significant different found between composite in longitudinal direction and transverse direction. Furthermore, the effect of volume fraction of fibre on mechanical and acoustic properties of composite was studied. All prepregs were fabricated using impregnation method, and compressed into different thicknesses, to vary the volume fraction of fibre. Then, the same mechanical, morphological and acoustic testings were carried out to characterize the composites. The tensile and flexural properties, as well as fracture toughness were found to be better in composites with higher volume fraction of fibre. However, the composites with lower volume fraction of fibre have better acoustic absorption. Apart from that, it was found that the anisotropy of fibres did not show significant effect on the mechanical properties of composites.